In Vivo Mn-Enhanced MRI for Early Tumor Detection and Growth Rate Analysis in a Mouse Medulloblastoma Model()() - Suero-Abreu, Giselle A. (Neoplasia, 2014)
Mouse models have increased our understanding of the pathogenesis of medulloblastoma (MB), the most common malignant pediatric brain tumor that often forms in the cerebellum. A major goal of ongoing research is to better understand the early stages of tumorigenesis and to establish the genetic and environmental changes that underlie MB initiation and growth. However, studies of MB progression in mouse models are difficult due to the heterogeneity of tumor onset times and growth patterns and the lack of clinical symptoms at early stages. Magnetic resonance imaging (MRI) is critical for noninvasive, longitudinal, three-dimensional (3D) brain tumor imaging in the clinic but is limited in resolution and sensitivity for imaging early MBs in mice. In this study, high-resolution (100 μm in 2 hours) and high-throughput (150 μm in 15 minutes) manganese-enhanced MRI (MEMRI) protocols were optimized for early detection and monitoring of MBs in a Patched-1 (Ptch1) conditional knockout (CKO) model. The high tissue contrast obtained with MEMRI revealed detailed cerebellar morphology and enabled detection of MBs over a wide range of stages including pretumoral lesions as early as 2 to 3 weeks postnatal with volumes close to 0.1 mm(3). Furthermore, longitudinal MEMRI allowed noninvasive monitoring of tumors and demonstrated that lesions within and between individuals have different tumorigenic potentials. 3D volumetric studies allowed quantitative analysis of MB tumor morphology and growth rates in individual Ptch1-CKO mice. These results show that MEMRI provides a powerful method for early in vivo detection and longitudinal imaging of MB progression in the mouse brain.